A comparison of transformation models between geodetic reference frames: case study in Illizi region (Algeria) - Haddad, Mahdi; Gahlouz, Mounia (Geodesy and Cartography, 2025)
The Illizi region is an important petroleum zone in Algeria, where various seismic surveys have been conducted. The merging of adjacent surveys is not possible due to incompatible data linked to the geodetic networks. In this study, the transformation of coordinates, from the global system (WGS84) to the local system based on the Clarke 1880 A spheroid, is carried out based on a set of 57 control points well distributed over the study area with coordinates determined in both the global and local systems. Five approaches were used to determine the transformation parameters between the two systems, namely: Geocentric Translation Model, Bursa-Wolf Transformation, Molodensky-Badekas Transformation, Abridged Molodensky transformation and Multiple Regression Equations (MRE). From statistics on the determined parameters and considering its advantage of reversibility, the Bursa-Wolf Transformation Model is the most suitable model to be used to transform coordinates between the two systems in the study area. Small amount of residuals in transformed coordinates using this model indicates acceptable Bursa-Wolf parameter estimation. An improvement in the results was observed after removing of the outliers control points detected using a statistical test. For the validation of the estimated parameters, external control points were used. The results show acceptable RMS in transformed coordinates of these points.